TEACHER'S STRATEGIES AND STUDENTS' RESPONSES IN TEACHING LISTENING SKILL IN THE LANGUAGE LABORATORY : A case study in a Junior High School in Tanjung Pinang - Sucahyo, Petrus Edi (2009)
This study is concerned with teacher's strategies and students' responses in teaching listening in the language lab. It used a case study research design involving one English teacher and seventy-two grade VII students of a junior high school in Tanjung Pinang conducted on February 12th-23rd, 2009. It aims to figure out teacher's strategies in teaching listening in the language laboratory, their strengths and weaknesses, and the students' responses toward teacher's strategies. It utilized a set of method to get data i.e. observation, interview, questionnaire, and supported by document analysis. The findings of this study show that the teacher has good understanding of strategies in teaching listening. The teacher's strategies in teaching listening in the language laboratory are relevant to the theory of language teaching highlighted by Lado (1979), Peterson (1991 as cited in Brown, 2001), Harmer (2001), Vandergrift (1996 in Rost, 2002), Berne in Osada (2004), Howatt and Dakin in Mohammed (2005),. Regarding the strengths of the strategies, the teacher could help the students more easily to master listening and speaking skills. The teacher believes that language laboratory is more effective and beneficial to teach English rather than in the classroom. The weaknesses of the strategies are caused by the teacher inability to operate the master control well. Besides, the difficulty is caused by the use of native-based cassettes and VCDs media as the students could not follow the speakers' pronunciation and intonation. However, the students are easier to comprehend the material of listening if it non-native voice or by the teacher herself. For this the teacher uses cassettes or CDs taken from Singapore. The students responded positively toward the English teacher's strategies. They felt interested, comfortable, and more active when they studied English in the language laboratory. They admitted that their knowledge of English especially listening and speaking skills had increased.